Pengaruh Insentif Terhadap Kinerja Pegawai Kantor Samsat Medan Utara - Wiranti Wiranti; Agung Suharyanto; Beby Masitho Batubara (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study aims to analyze and measure the impact of incentives on employee performance at Kantor Samsat Medan Utara. Using a descriptive quantitative approach and questionnaire methods, the study applies Product Moment Correlation to identify the relationship between incentives and performance, a Determination Test to measure the effect size, and linear regression to predict outcomes. Based on the results of data analysis, the level of incentive provision for North Medan UPT Samsat Office employees is included in the high category, namely 47.9%. The performance level of North Medan UPT Samsat Office employees is included in the high category, namely 40.6%. Next, we obtained the results of the relationship between providing incentives and employee performance. Based on the research results, a value of 0.369 was also obtained, thus the calculated rxy value was greater than the r value of the product moment table, namely 0.369>0.198. Apart from that, from the results of the calculation above, it can be seen that the coefficient of determination is 0.136, so that the influence of providing incentives on employee performance is 13.6%, while the remaining 86.4% is caused by other factors, as for the linear regression equation in this study is Y = 19.355 + 1.380